Nanoindentation of Nanoglasses Tested by Molecular Dynamics Simulations: Influence of Structural Relaxation and Chemical Segregation on the Mechanical Response - Adjaoud, Omar; Albe, Karsten (Frontiers in Materials, 2021)
We present molecular dynamics simulations of nanoindentation in order to investigate the effects of segregation and structural relaxation on the mechanical properties of Cu64Zr36 nanoglasses prepared by particle consolidation and long-time annealing. Our analysis of load-displacement curves shows that the effective elastic modulus of nanoglasses is lower than that of their homogeneous metallic glass counterpart. This is mainly because of the defective short-range order present in the glass-glass interface, but to a lesser extend due to chemical inhomogeneities. Structural relaxation obtained by long-time annealing (500 ns) at 0.8 Tg leads to a shift from a homogeneous deformation to a mix of homogeneous deformation and shear bands. The obtained hardness values of annealed nanoglass are comparable to those of homogenous glass samples, but significantly higher as compared to juvenile as-prepared nanoglass samples. The results are discussed in the context of recent nanonindentation experiments.